Joseph Torrence correspondence - Torrence, Joseph
ALS (Pittsburgh) written by Torrence to Gov. Thomas Mifflin relating to Pennsylvania militia.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Mifflin, Thomas, -- 1744-1800 -- Correspondence; Pennsylvania -- History -- 1775-1865.; Pennsylvania -- Militia; Pittsburgh (Pa.) -- History; Army officers